Environmental awareness level on Setiu Wetlands in Terengganu, Malaysia - Haron, Dr. Nazatul Faizah; Ab Ghani, Dr. Hartini; Mohd Noor, Dr. Noor Aina Amirah; Aziz, Iskandar (Kaizentrenovation Sdn Bhd, 2020)
Environmental awareness is defines as human behavior's attitude to the environmental impacts and and how with attitude knowledge of environment respond to the environmental issues. Implementation of New Ecological Paradigm (NEP) Scale is assumes as a significant tool to measure environmental attitude with 5-point Likert scale comprised of 15 items or statements about the relationship between humans and the environment. This study proposes identification of environmental awareness level towards Setiu Wetlands in Terengganu and demonstrates the relationship of wetland background and wetland issues towards environmental awareness from the view of local people in Setiu, Terengganu. Random sampling measures was using for questionnaires survey and descriptive analyzed and inffered to explain the relationship in this study by using factor analysis procedures.